Involvement of Host Cell Integrin α2 in Cryptosporidium parvum Infection - Zhang, Haili (American Society for Microbiology, 2012)
Cryptosporidium parvum is an opportunistic pathogen in AIDS patients. It is an intracellular but extracytoplasmic parasite residing in a host cell-derived parasitophorous vacuole. It is still poorly understood how this parasite interacts with host cells. We observed that expression of the integrin α2 (ITGA2) gene in host cells was significantly upregulated upon C. parvum infection, and a higher level of ITGA2 protein was present in the parasite infection sites. The infection could be reduced by the treatment of antibodies against ITGA2 and integrin β1 (ITGB1) subunits, as well as by type I collagen (an integrin α2β1 ligand). We also generated stable knockdown of ITGA2 gene expression in HCT-8 cells and observed consistent reduction of parasite infection in these knockdown cells. Collectively, our evidence indicates that host cell ITGA2 might be involved in interacting with Cryptosporidium during infection, probably acting as part of the regulatory elements upstream of the reported recruiting and reorganization of F actin at the infection sites.